Differences of Correlation Factors of Depression Among The Senior Citizens who Live with Their Family and Those who Live in Nursing Home - Weddy Martin; Achir Yani; Reni Dayati (Faculty of Nursing, Universitas Andalas, 2018)
Background: The number of senior citizen in Indonesia, wheter the ones who live with their family or in a nursing home, is increasing. The changes they face in their elderly life lead to depression. Depression is a common mental health problems found in the elderly. Purpose: To analyze the differences of correlation factors of depression among the senior citizens who live with their family and those who live in Nursing Home. Method: The design of the study is descriptive analytic with cross sectional approach. The subject of the study were 74 senior citizens who live with their family and also 74 senior citizen who live in nursing home. The sample was taken by using total sampling technique. Results: The statistical test showed that there was a correlation of depression factors between the depression on the senior citizens who live with their family and those who live in a nursing home. There also were differences of depression factors between depression on senior citizens who live with their family and those who live in a nursing home. Conclusions: Based on the study, Nursing Home is suggested to improve its service quality on elderly care. For families with senior citizens, it is suggested to give more attention and care to the elderly with depression and to prevent depression for the elderly with no depression.